Urban planning policy and clean energy development Harmony- evidence from smart city pilot policy in China. (July 2023) - Chen, Pengyu; Dagestani, Abd Alwahed
Abstract: Rapid urbanization is affecting the harmonious development of the environment and economy. Governments are developing new urban planning policies to achieve sustainable urban development. Using the Chinese smart city pilot policy as a natural experimental group, we use a difference-differences model to explore the relationship between smart cities and clean energy development. There are three findings in this paper. First, we find that smart city pilots drive clean energy development. Second, we find that digital technologies can reinforce the positive impact of smart city pilots and that innovation and financial inclusion have a positive mediating role. Third, we find that the impact of smart city pilots has a heterogeneous impact. Namely, pilots in coastal, large, and resource-based cities have a more positive impact on clean energy development. Existing smart city pilots significantly impact energy security and sustainable development. Our study provides a new perspective on urban planning and clean energy development in emerging countries such as China. Highlights: A difference-differences model to explore the effect of smart city pilot. Smart city pilot drives clean energy development. Innovation and financial inclusion have positive mediating roles. Digital technology has a positive moderating effect. Clean energy development in smart cities is distinctly heterogeneous.